Women's Cultural Center – Jenin - زينه الطاهر (My University, 2025)
This project envisions the design of a cultural center dedicated to women and girls in Palestine, specifically in the city of Jenin. The center aims to provide a multifunctional space that meets the diverse needs of women and contributes to strengthening their roles within society. It offers a safe and inspiring environment that combines culture, entertainment, education, and sports. The facility includes various sections such as a library, seminar and classroom spaces, a theater, children’s areas, and green outdoor spaces. The center is named "Tarbeyza", inspired by Palestinian heritage. The word Tarbeyza refers to a small table, which historically served as a gathering point for Palestinian women inside homes due to the lack of public spaces. Around this table, women would engage in social interaction, cultural exchange, and play traditional games such as Al-Bargis. The name symbolizes one of the earliest forms of communal entertainment and social bonding among women. The design of the center is based on principles of comfort, sustainability, and inclusivity, aiming to provide a rich and holistic experience for women of all ages and backgrounds. Ultimately, the project aspires to contribute to community development by empowering women and supporting their active role in shaping society.